Pós-modernidade, ambientalismo e Partido Verde: dilemas políticos na contemporaneidade - Viviani, Ermeli Damazo (2009)
The present work aims to point at the existing relations between the rise of the post-modern condition, the development of a worldwide agenda for the environment, and hence the institutionalization of the environment issues. For the latter, we can point some processes such as: the realization of international summits, the creation of international organizations with the sole purpose of dealing with the environment, the commitment of national governments, and also the environment issue party-building process. Post-modernity represents, in its sense, the crisis of modernity, based on the Enlightenment values. The search for human emancipation, in accordance with the universal albeit restrained notion of progress and science resulted in extremely harmful consequence to the environment. The strengthening of the concept of postmodernity came as a result from the capitalistic systemic re-positioning (which took place during the flexible accumulation system, during the 1970s and forth that has resulted in many cultural changes), together with the crumbling of the soviet socialism and the so-called social fragmentation. The latter is represented by the multiplicity of social actors as legitimate vectors of political processes. Therefore, our main general hypothesis relates the condition of post-modernity as sponsor to environmental themes and crucial for the process of institutionalization and internationalization of the environmental agenda. Furthermore, the post-modernity condition has also rendered the worsening of the ecological problem, the fostering of new kinds of socio-political mobilization that brought the attention of the international community to the matter